Impact of bivalirudin on post-procedural epicardial blood flow, risk of stent thrombosis and mortality after percutaneous coronary intervention - Fiedler, K. Anette; Ndrepepa, Gjin; Schulz, Stefaniec; Floh, Simone; Hoppmann, Petra; Kufner, Sebastian; Bernlochner, Isabell; Byrne, Robert A; Schunkert, Heribert; Laugwitz, Karl-Ludwig; Kastrati, Adnan (EuroIntervention, 2016)
Aims: We aimed to assess the association of bivalirudin with post-procedural Thrombolysis In Myocardial Infarction (TIMI) flow, acute (≤24 hours) and 30-day stent thrombosis (ST), and one-year mortality. Methods and results: The study included 11,623 patients undergoing percutaneous coronary intervention (PCI). The primary outcomes were post-procedural TIMI flow grade ≤2 and definite acute ST. In groups treated with bivalirudin (n=3,135), abciximab plus unfractionated heparin (UFH; n=3,539) and UFH alone (n=4,949), post-procedural TIMI was ≤2 in 5.2%, 3.2% and 3.2% of patients, respectively (adjusted odds ratio [OR]=1.96 [95% confidence interval] 1.47-2.56 for bivalirudin versus abciximab plus UFH and OR=1.56 [1.20-2.04] for bivalirudin versus UFH). Definite acute ST occurred in two patients (0.06%) treated with bivalirudin, two patients (0.06%) treated with abciximab plus UFH, and seven patients (0.14%) treated with UFH (p=0.47). Bivalirudin was not associated with increased risk of 30-day ST (hazard ratio [HR]=1.20 [0.59-2.43] versus abciximab plus UHF, and HR=0.93 [0.48-1.82] versus UFH) or one-year mortality (HR=0.95 [0.70-1.28] versus abciximab plus UHF, and HR=1.05 [0.78-1.41] versus UFH). Conclusions: Bivalirudin was associated with higher risk of suboptimal post-PCI TIMI flow but not with increased risk of acute or 30-day definite ST or one-year mortality compared with abciximab plus UFH or UFH alone.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bivalirudin; Mortality; Percutaneous coronary intervention; Stent thrombosis; TIMI flow